CLINICAL ANATOMY OF THE INTERCRURAL FIBERS (FIBRAE INTERCRURALIS) - Тараско, Андрей Дмитриевич; Азаров, Павел Алексеевич (Medicine in Kuzbass, 2025)
In the available literature, there are isolated works that indicate the clinical significance of intercrural fibers (fibrae inercruralis) (IF). Objective – to study and describe the clinical anatomy of the IF. Methods. The clinical anatomy of the IF was studied using anatomical dissection as part of a standard pathology study on 104 corpses of both sexes (67 men, 37 women). Results. It was found that IF occurs in 88-90% of cases in the studied material (on the right and on the left, respectively). In the structure of IF, there are both fibers of dense, shaped connective tissue and unformed connective tissue . Arterial vessels are found on the periphery of the IF. In 30% of cases, they are characterized by asymmetry of structure, the predominance of weakly expressed forms for women and young people and pronounced forms for men of mature and elderly age. For women and men of mature age, the overlapping of the boundaries of the deep inguinal ring by the IF is characteristic. Conclusion. The IF can be a structure that resists an increase in intra-abdominal pressure, especially in males, mature and elderly people.